Optimism, coping and childhood cancer: A descriptive study - Castellano-Tejedor, Carmina (Psicooncología, 2015)
Purpose and methods: This study is aimed to assess optimism in the worst self-reported moments of the oncological process in a sample of adolescent survivors of childhood cancer (N=41). It will also explore whether this optimism is associated with coping in such situations as well as with health-related quality of life (HRQoL) in survival. Results: Up to 70.7% of the sample referred to be optimistic in the worst situations of the illness. Those adolescents considered as “pessimistic” showed greater use of “self-blame” and “seek for spiritual support” strategies. However, it could not be observed a significant relationship between optimism and coping in the worst self-reported situations, and only one significant relationship was identified between optimism and the “physical well-being” dimension of HRQoL. Conclusions: It could not be identified a clear effect of optimism displayed during cancer and HRQoL in survival period. Thus, it is possible that optimism might be a necessary condition to face difficulties in a more adaptative manner during the illness, but not sufficient to have a significant effect on resulting HRQoL after cancer remission. It is even probable that optimism may facilitate the occurrence of other variables that could have a more significant effect on HRQoL in survivorship. More research with childhood population is needed to further clarify these relationships.